Generative Artificial Intelligence in Higher Education: Analysing the Impact of Perceived Ease of Use and Usefulness on AI Technology Adoption Among University Students in Azerbaijan - Muduve, Joyce Lisa (ADA University, 2024)
This study investigated the use of Generative Artificial Intelligence tools by university students in Azerbaijan through the lens of the Technology Acceptance Model. The research explored student perceptions of ease of use and usefulness of Generative artificial intelligence tools, their influence on actual usage, and student perspectives on the future role of artificial intelligence in education. The findings revealed positive correlations between perceived ease of use, perceived use, and actual uses. Regression analysis confirmed that both perceive ease of use and perceived use significantly predict students' actual use of Generative AI tools. The data obtained on student motivations for using artificial intelligence tools identified information access, comprehension, study efficiency, and assessment preparation as key factors. Notably, a significant portion of students reported using artificial intelligence for critical thinking tasks at least occasionally. These findings support Technology Acceptance Model and suggest that user-friendly and valuable artificial intelligence tools can be effectively integrated into educational settings. The study highlights the potential of artificial intelligence to enhance learning experiences and student outcomes. Based on these findings, the research recommends strategies for universities to promote responsible artificial intelligence integration in curricula, assessment practices, and ethical considerations.
Keywords: Artificial intelligence -- Study and teaching -- Azerbaijan.; University students -- Attitudes -- Azerbaijan; Information technology -- Study and teaching -- Azerbaijan; Azerbaijan -- Education -- Technology.; Education